Association of ten gastrointestinal and other medical conditions with positivity to faecal occult blood testing in routine screening: a large prospective study of women in England. (21st January 2019) - He, Emily; Alison, Rupert; Blanks, Roger; Pirie, Kirstin; Reeves, Gillian; Ward, Robyn L; Steele, Robert; Patnick, Julietta; Canfell, Karen; Beral, Valerie; Green, Jane
Abstract: Background: In 2006, the Bowel Cancer Screening Programme (BCSP) in England began offering biennial faecal occult blood testing (FOBt) at ages 60–69 years. Although FOBt is aimed at detecting colorectal neoplasms, other conditions can affect the result. In a large UK prospective study, we examined associations, both before and after screening, between FOBt positivity and 10 conditions that are often associated with gastrointestinal bleeding. Methods: By electronically linking BCSP and Million Women Study records, we identified 604 495 women without previous colorectal cancer who participated in their first routine FOBt screening between 2006 and 2012. Regression models, using linked national hospital admission records, yielded adjusted relative risks (RRs) in FOBt-positive versus FOBt-negative women for colorectal cancer, adenoma, diverticular disease, inflammatory bowel disease, haemorrhoids, upper gastrointestinal cancer, oesophagitis, peptic ulcer, anaemia and other haematological disorders. Results: RRs in FOBt-positive versus FOBt-negative women were 201.3 (95% CI 173.8–233.2) for colorectal cancer and 197.9 (95% CI 180.6–216.8) for adenoma within 12 months after screening and 3.49 (95% CI 2.31–5.26) and 4.88 (95% CI 3.80–6.26), respectively, 12–24 months after screening; P < 0.001 for all RRs. In the 12 months after screening, the RR for inflammatory bowel disease was 26.3 (95% CI 19.9–34.7), and ranged between 2 and 5 for the upper gastrointestinal or haematological disorders. The RRs of being diagnosed with any of the eight conditions other than colorectal neoplasms before screening, and in the 12–24 months after screening, were 1.81 (95% CI 1.81–2.01) and 1.92 (95% CI 1.66–2.13), respectively. Conclusions: Whereas FOBt positivity is associated with a substantially increased risk of colorectal neoplasms after screening, eight other gastrointestinal and haematological conditions are also associated with FOBt positivity, both before and after screening.